Surgical outcome of canal wall down mastoidectomy with or without cavity obliteration - Alam, Mohammad Shamsul; Shaheen, M. Mazharul; Alam, M. Sahbub; Rahman, Mohammad Mostafizur; Tanu, Tanni Kundu (International Journal of Research in Medical Sciences, 2026)
Background: Canal wall down (CWD) mastoidectomy is commonly used to treat chronic otitis media with cholesteatoma. Cavity obliteration may improve postoperative outcomes by reducing cavity-related complications. Aim of the study was to compare surgical outcomes of CWD mastoidectomy with and without cavity obliteration. Methods: This prospective longitudinal observational study was conducted at Sir Salimullah Medical College Mitford Hospital, Dhaka, from July 2023 to June 2024. Eighty patients with active squamous chronic otitis media undergoing CWD mastoidectomy were enrolled. Group I had no obliteration; group II underwent obliteration using vascularized periosteo-temporofascial swing, bone dust, and cartilage. Outcomes included cavity discharge, giddiness, epithelialisation, wax formation, hearing, meatal stenosis, residual cholesteatoma, and facial nerve palsy. Results: Mean age was comparable (27.92±8.23 versus 27.28±8.19 years; p=0.724), with male predominance in both groups. At three months, dry cavity was achieved in 95.0% of group II versus 72.5% of group I (p=0.015). Persistent giddiness was lower in group II (2.5%) than group I (20.0%). Complete epithelialisation occurred in 90.0% of group II versus 60.0% of group I (p=0.004). Wax formation was lower in group II (5.0%) than group I (20.0%). Postoperative hearing was significantly better in group II (45.82±5.38 dB versus 48.22±4.07 dB; p=0.027), with greater hearing gain (10.22±5.42 dB versus 7.95±3.68 dB; p=0.031). Meatal stenosis and residual cholesteatoma were less frequent in group II, and no facial nerve palsy occurred. Conclusions: Cavity obliteration in CWD mastoidectomy provides better postoperative outcomes, including improved cavity healing, reduced complications, and superior hearing improvement.